A estética da dissonância nas obras de Charlotte Brontë - Patricia Carvalho Rocha (2008)
Charlotte Brontë (1816-1855), one of the most prominent figures in the questioning of the ideology of the feminine in the literature of the nineteenth century, shows in her works not only a concern with the arbitrariness of the notion of gender, but also a discussion about this notion through the portrayal of protagonists that can be said to be dissonant in the relation to the ideology of the period. In The Professor, Jane Eyre, Shirley and Villette, Brontë portrays characters that do not conform to idealized notions of gender in the period and that explicitly reflect upon the established parallelism between sex and gender, questioning the subservient position ascribed to women in society. With a view to presenting a more contemporary reading of Brontës work, I focus on gender theories that emphasize social and performance aspects, especially Judith Butlers concept of gender as performance, in my reading of Brontës novels. These works require an analysis based on new paradigms that might encompass the fragmentation and multiplicity of the possibilities of performance regarding issues of gender, as presented by the author.